Safety and immunogenicity of inactivated SARS-CoV-2 vaccine in high-risk occupational population: a randomized, parallel, controlled clinical trial - Yongliang Feng; Jing Chen; Tian Yao; Yue Chang; Xiaoqing Li; Rongqin Xing; Hong Li; Ruixue Xie; Xiaohong Zhang; Zhiyun Wei; Shengcai Mu; Ling Liu; et al. (BMC, 2021)
Abstract Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and the resulting coronavirus disease 2019 (COVID-19) have a substantial burden on health-care systems around the world. This is a randomized parallel controlled trial for assessment of the immunogenicity and safety of an inactivated SARS-CoV-2 vaccine, aiming to determine an appropriate vaccination interval of the vaccine for high-risk occupational population. Methods In an ongoing randomized, parallel, controlled phase IV trial between January and May 2021 in Taiyuan City, Shanxi Province, China, we randomly assigned the airport ground staff and public security officers aged 18 to 59 years to receive two doses of inactivated SARS-CoV-2 vaccine at 14 days, 21 days, or 28 days. The serum neutralizing antibody to live SARS-CoV-2 was performed at baseline and 28 days after immunization. Long-term data are being collected. The primary immunogenicity endpoints were neutralization antibody seroconversion and geometric mean titer (GMT) at 28 days after the second dose. Analysis of variance (ANOVA), chi-square, and logistic regression analysis were used for data analysis. Results A total of 809 participants underwent randomization and received two doses of injections: 270, 270, 269 in the 0-14, 0-21, and 0-28 vaccination group, respectively. By day 28 after the second injection, SARS-CoV-2 neutralizing antibody of GMT was 98.4 (95% CI: 88.4-108.4) in the 0-14 group, which was significantly lower compared with 134.4 (95% CI: 123.1-145.7) in the 0-21 group (P < 0.001 vs 0-14 group) and 145.5 (95% CI: 131.3-159.6) in the 0-28 group (P < 0.001 vs 0-14 group), resulting in the seroconversion rates to neutralizing antibodies (GMT ≥ 16) of 100.0% for all three groups, respectively. The intention-to-treat (ITT) analysis yielded similar results. All reported adverse reactions were mild. Conclusions Both a two-dose of inactivated SARS-CoV-2 vaccine at 0-21 days and 0-28 days regimens significantly improved SARS-CoV-2 neutralizing antibody level compared to the 0-14 days regimen in high-risk occupational population, with seroconversion rates of 100.0%. Trial registration Chinese Clinical Trial Registry, ChiCTR2100041705, ChiCTR2100041706. Registered 1 January 2021, www.chictr.org.cn . Graphical Abstract